2015
DOI: 10.5121/ijsea.2015.6105
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Evaluation of Impact of Refactoring on Internal and External Measures of Code Quality

Abstract: Refactoring is the process of improving the design of existing code by changing its internal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
(26 reference statements)
0
11
0
1
Order By: Relevance
“…The results showed that applying refactoring methods in different order provide different effects on code. The main goal of the study in [15] is to assure or not assure if refactoring develop software quality and it was applied on the internal and external measures. The experiment applied on c# open source project and visual studio was the selected tool.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that applying refactoring methods in different order provide different effects on code. The main goal of the study in [15] is to assure or not assure if refactoring develop software quality and it was applied on the internal and external measures. The experiment applied on c# open source project and visual studio was the selected tool.…”
Section: Related Workmentioning
confidence: 99%
“…Refactoring is a technique to restructure software by applying a series of methods without changing its observable behavior and to make software easier to understand and cheaper to modify [1]. Refactoring can improve the code quality of a software, including readability, reusability and maintainability [2][3][4]. Code extraction is one of the frequently-used refactoring skills and is also an important operating step for other complex refactoring methods, such as Extract Class, Replace Type Code with Subclasses, Replace Type Code with State/Strategy, Form Template Method, etc.…”
Section: Introductionmentioning
confidence: 99%
“…At present, most of the existing code extraction methods are based on Mark Weiser's program slicing [9][10] and follow three principles proposed by Nikolaos Tsantalis [11], that is, (1) for declared variables, the code segment extracted must include their complete calculation procedures, (2) the behaviors of the program before and after extraction must be consistent, and (3) the code segment extracted should not reappear in the method after extraction. Nikolaos Tsantalis divided program slices into two types: the complete computation slices and the object state slices.…”
Section: Introductionmentioning
confidence: 99%
“…A further challenge is that while it may appear that introducing design patterns, improving software quality metrics, and removing code smells are all noncompeting goals and hence can be simultaneously optimized, empirical evidence indicates otherwise. Studies by Soetens and Demeyer, Stroggylos and Spinellis, and Kannangara and Wijayanayake all found little or no correlation between refactoring activity and improvement in software quality metrics. In a similar vein, Wilking et al found that refactored code was neither more maintainable nor easier to modify than unrefactored versions of the same code.…”
Section: Introductionmentioning
confidence: 99%